SHoes for Adolescent PatEllofemoral pain: study protocol for the SHAPE Australian community-based, randomised clinical trial - Kim L Bennell; Kade L Paterson; Rana S Hinman; Jo-Anne Manski-Nankervis; Adam Bryant; Karen Elaine Lamb; Peixuan Li; Sam Shearer; Anurika P De Silva (BMJ Open)
Introduction Patellofemoral pain affects one-third of adolescents, with most experiencing symptoms into adulthood. Guidelines recommend exercise and foot orthoses based on clinical trials in adults; however, these approaches have been found to be ineffective and have poor adherence in adolescents. ‘Minimalist’ shoes can reduce patellofemoral joint forces in adults; and may therefore be a promising low burden management approach for patellofemoral pain. This article outlines the protocol for a randomised clinical trial (RCT) that aims to determine if minimalist footwear improves pain, function and other symptoms compared with motion control shoes, in adolescents with patellofemoral pain.Methods and analysis This is a 3-month, pragmatic, two-arm parallel group, comparative effectiveness, superiority RCT conducted in Melbourne, Australia. We are recruiting 158 participants aged between 12 and 19 years with patellofemoral pain from the community. Following baseline assessment, participants are randomised to receive either minimalist shoes (intervention group) or motion control shoes (control group, given that clinicians typically advocate motion control shoes for patellofemoral pain). Participants choose one pair of shoes in their allocated group from two colour options. They are advised to wear their study shoes for all planned sports and exercise-based activities over the subsequent 3 months and are also advised that they may wear them as much as desired at other times. The primary outcomes are the 3-month change in (1) severity of the worst knee pain experienced over the past week, measured using a Numerical Rating Scale, and (2) the function in sport and play subscale of the Knee Injury and Osteoarthritis Outcome Score for Children. The secondary outcomes include changes in other parameters of knee pain, symptoms, function in daily activities, health-related and knee-related quality of life, global improvement and fear of movement. Other measures include cointervention use, adherence, adverse events, shoe comfort, descriptive characteristics, physical activity levels, footwear characteristics and objective foot measures.Ethics and dissemination This study has been approved by the University of Melbourne Greater than Low Risk Human Research Ethics Committee (reference: 2022-25470-35344-4). Written informed consent is obtained from each participant prior to enrolment. The SHoes for Adolescent PatEllofemoral pain trial will provide the first RCT evidence on the efficacy of minimalist shoes compared with motion control shoes in adolescents with patellofemoral pain. Outcomes will be presented at national and international scientific conferences and published in peer-review journals.Trial registration number Australian New Zealand Clinical Trials Registry reference: ACTRN12623000042640.